An intervention to reduce playground equipment hazards. Issue 2 (1st June 1999) - Roseveare, Christine A; Brown, Judith M; McIntosh, Jillian M Barclay; Chalmers, David J
Abstract : Objectives —A community intervention trial was carried out to evaluate the relative effectiveness of two methods of reducing playground hazards in schools. The study hypotheses were: (1) a health promotion programme addressing barriers to implementing the New Zealand Playground Safety Standard will reduce playground hazards and (2) the intervention programme will be more successful than providing information alone. Methods —Twenty four schools in Wellington, New Zealand were randomly allocated into two groups of 12 and their playgrounds audited for hazards. After the audit, the intervention group received a health promotion programme consisting of information about the hazards, an engineer's report, regular contact and encouragement to act on the report, and assistance in obtaining funding. The control group only received information about hazards in their playground. Results —After 19 months, there was a significant fall in hazards in the intervention schools compared with the control schools (Mann-Whitney U test, p=0.027). No intervention schools had increased hazards and eight out of 12 had reduced them by at least three. In contrast, only two of the control schools had reduced their hazards by this amount, with three others increasing their hazards in that time. Conclusions —It is concluded that working intensively with schools to overcome barriers to upgrading playground equipment can lead to a reduction in hazards, and that this form of intensive intervention is more effective than providing information alone.